Respuesta :
y = 5secx - 10cosx
y' = 5secxtanx + 10sinx
m at (3, 5) = 5sec(π/3)tan(π/3) + 10sin(π/3) = 5(2)(√3) + 10(√3/2)
m = 6√3 + 5√3 = 11√3
y - 5 = 11√3(x - π/3)
y = 11√3 x - 33π√3 + 5
y' = 5secxtanx + 10sinx
m at (3, 5) = 5sec(π/3)tan(π/3) + 10sin(π/3) = 5(2)(√3) + 10(√3/2)
m = 6√3 + 5√3 = 11√3
y - 5 = 11√3(x - π/3)
y = 11√3 x - 33π√3 + 5
The equation of a line is normally of the form:
y = mx + b ; where m = slope and b = y integer
The derivative of a function is the slope at any given point so:
m = f'(x); and the point itself is used to calibrate the rest
Tangent line = f'(x0) (x -x0) + y0 ;
where x0 and y0 are the components for the point being used
So,
m = f'(pi/3)
= f'(1.04)
b = -f'(pi/3)*(pi/3) + 5
=-f'(1.0816) +5
y = mx + b ; where m = slope and b = y integer
The derivative of a function is the slope at any given point so:
m = f'(x); and the point itself is used to calibrate the rest
Tangent line = f'(x0) (x -x0) + y0 ;
where x0 and y0 are the components for the point being used
So,
m = f'(pi/3)
= f'(1.04)
b = -f'(pi/3)*(pi/3) + 5
=-f'(1.0816) +5